EUROPEAN GUIDELINES ON CARDIOVASCULAR DISEASE PREVENTION IN CLINICAL PRACTICE - G. De Backer; E. Ambrosioni; K. Borch-Johnsen; C. Brotons; R. Cifkova; J. Dallongeville; S. Ebrahim; O. Faergeman; I. Graham; G. Mancia; V. Manger Cats; K. Orth-Gomer; et al. (Рациональная фармакотерапия в кардиологии, 2015)
European guidelines on cardiovascular disease prevention in clinical practice.